2014
DOI: 10.1111/jgh.12572
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microwave ablation and surgical resection for treatment of hepatocellular carcinomas conforming to Milan criteria

Abstract: MWA results in lower DFS rates than RES for HCC conforming to Milan criteria. However, the OS rates are comparable between the two therapies. For solitary HCC ≤ 3 cm, MWA is as effective as RES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 40 publications
(102 reference statements)
2
45
0
Order By: Relevance
“…3034 So far, only 2 randomized trials have compared MWA with resection and RFA. 30,34 In the RCT that compared RFA with percutaneous microwave coagulation, no significant differences were observed between these 2 procedures in terms of therapeutic effects, complication rates, and rates of residual foci of untreated disease.…”
Section: Hcc Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…3034 So far, only 2 randomized trials have compared MWA with resection and RFA. 30,34 In the RCT that compared RFA with percutaneous microwave coagulation, no significant differences were observed between these 2 procedures in terms of therapeutic effects, complication rates, and rates of residual foci of untreated disease.…”
Section: Hcc Treatmentmentioning
confidence: 99%
“…3034 So far, only 2 randomized trials have compared MWA with resection and RFA. 30,34 In the RCT that compared RFA with percutaneous microwave coagulation, no significant differences were observed between these 2 procedures in terms of therapeutic effects, complication rates, and rates of residual foci of untreated disease. 30 In a recent randomized study that evaluated the efficacy of MWA and resection in the treatment of HCC conforming to Milan criteria, MWA was associated with lower disease-free survival (DFS) rates than resection with no differences in OS rates.…”
Section: Hcc Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For HCCs that meet these criteria, primary technique effectiveness is high (93-99%) and LTP rates are low (5.2-10.2%) (26,28,29). A summary of overall survival rates and local tumor progression from multiple studies can be found in Table 1 .…”
Section: Current Literature On Treating Primary and Secondary Liver Cmentioning
confidence: 99%
“…From a phase III randomised controlled trial, MWA had similar results compared with RFA in hepatocellular carcinoma (HCC) patients, but with fewer sessions, fewer applicator puncture, shorter ablation durations and lower hospitalisation cost [10]. In addition, multiple studies reported that the clinical outcomes of MWA application in the liver and renal tumour were similar to surgery when the tumour was less than 3 cm [11,12]. However, studies on the therapeutic effect of MWA versus lobectomy in stage I NSCLC remain rare.…”
Section: Introductionmentioning
confidence: 99%